2022
DOI: 10.1159/000528653
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Extraction Methodology to Analyse Potential Inflammatory Biomarkers from Sebum

Abstract: Introduction: Proteins, such as cytokines and chemokines, are present in varying concentrations in a range of biofluids, with an important signalling role in maintaining homeostasis. Commercial tapes have been employed to non-invasively collect these potential biomarkers in sebum from the skin surface to examine their concentrations in conditions including acne, atopic dermatitis and pressure ulcers. However, the identification of robust biomarker candidates is limited by the low abundance of specific protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Findings from a recent study indicated an increase in IL-1α when skin was in contact with pads moistened with 0.9% saline solution alone; however, no differences in the expression of low abundance proteins (TNF-α, IL-6, and IL-8) were detected 12. These discrepancies in study findings may also be attributed to our use of an optimized method of extraction involving both chemical and mechanical stimuli 29…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Findings from a recent study indicated an increase in IL-1α when skin was in contact with pads moistened with 0.9% saline solution alone; however, no differences in the expression of low abundance proteins (TNF-α, IL-6, and IL-8) were detected 12. These discrepancies in study findings may also be attributed to our use of an optimized method of extraction involving both chemical and mechanical stimuli 29…”
Section: Discussionmentioning
confidence: 66%
“…12 These discrepancies in study findings may also be attributed to our use of an optimized method of extraction involving both chemical and mechanical stimuli. 29…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the cytokines profiles following insults have reported changes in high‐abundant cytokines, such as IL‐1α and IL‐1RA 14,16 . However, with the use of the new extraction protocol, we were able to quantify low‐abundant cytokines, such as IL‐8 and G‐CSF that could provide a classification of damaged skin from healthy skin 22 . It is well known that a variety of skin insults (mechanical, chemical and thermal) alters the production of the high‐abundant cytokines, namely, IL‐1α and IL‐1RA 12 .…”
Section: Discussionmentioning
confidence: 91%
“… 14 , 16 However, with the use of the new extraction protocol, we were able to quantify low‐abundant cytokines, such as IL‐8 and G‐CSF that could provide a classification of damaged skin from healthy skin. 22 It is well known that a variety of skin insults (mechanical, chemical and thermal) alters the production of the high‐abundant cytokines, namely, IL‐1α and IL‐1RA. 12 In addition, each of the low‐abundant cytokines plays a unique role in maintaining the barrier function, for example, TNF‐α, INF‐γ and IL‐1β are important in lipid synthesis, whereas IL‐8 and G‐CSF are associated with dendritic cell migration and neutrophil regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation